PRACTICE OF MONEY LOAN AGREEMENT IN LHOK KEUTAPANG VILLAGE PIDIE DISTRICT UNDER ISLAMIC ECONOMIC LAW - Husna, Asmaul; Yusriana (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
In Islam, when murtahin gives debt to rahin, it is not justified to take benefits or additions to the debt. This is because al-rahn is a tabarru' contract which is a mutual assistance contract without any reward and solely to expect the pleasure and reward of Allah, not to seek personal gain or additional income. In reality, the practice of a money loan agreement with motorcycle collateral in Lhok Keutapang Village, Pidie Subdistrict, Pidie Regency, where the murtahin provides debt with motorcycle collateral with the intention of seeking profit, and requires additional debt. The formulation of this research problem is how the practice of money loan agreements with motorcycle collateral in Lhok Keutapang Village, Pidie Subdistrict, Pidie Regency, and how the analysis of late fees in this practice. This research uses the type of field research with descriptive analysis, through data collection techniques, namely observation, interviews and documentation. The results showed that debt and credit in this village is done verbally on the basis of mutual trust. In practice where rahin owes money in the amount of Rp.2,000,000 which will be paid in three months, and within this period rahin submits his motorcycle as collateral. And murtahin gives conditions to rahin if the debt is not paid within the agreed time period, there will be a fine for the delay of Rp.300,000. Also according to the concept of rahn, the practice of money loan agreements with motorcycle collateral that occurs in Lhok Keutapang village is contrary to Islamic law because it is included in the practice of loan sharks. Therefore, this kind of debt and credit practice must be stopped or there must be a policy from the village apparatus.